2014
DOI: 10.1097/mao.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Synkinesis by Biofeedback Therapy

Abstract: Biofeedback therapy is more efficient than common physiotherapy. By using this approach, controlling and reducing synkinesis is more feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 15 publications
0
17
0
2
Order By: Relevance
“…Assessment 10 months later showed that the rate of synkinesis was significantly lower in the biofeedback treatment group than in the control group. Pourmomeny et al. (2014) also confirmed that EMG biofeedback might lower the rate and degree of synkinesis.…”
Section: Managementmentioning
confidence: 52%
“…Assessment 10 months later showed that the rate of synkinesis was significantly lower in the biofeedback treatment group than in the control group. Pourmomeny et al. (2014) also confirmed that EMG biofeedback might lower the rate and degree of synkinesis.…”
Section: Managementmentioning
confidence: 52%
“…Neuromuscular re-education based on brain neuroplasticity could be an appropriate method ( 6 ). However, this method should be proportional according to the limitations of proprioception in the facial muscles ( 25 ).Therefore EMG biofeedback, requiring considerable skill compared with exercise therapy, could be a suitable method and an effective instrument in controlling synkinesis and creating coordination between the two sides of the face ( 14 , 28 , 29 ). In future studies, we would recommend comparing the direct influence of BTX and biofeedback therapy on the sequelae of facial nerve palsy, as well as evaluating the effect when BTX is injected directly into the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Common interventions include surgery (neurolysis and myoctomy) and rehabilitation ( 8 ), including physical therapy modalities. Biofeedback (mirror and electromyography [EMG]) for neuromus- cular re-education has been shown to be the most effective intervention ( 8 , 9 , 14 , 15 ). However, biofeedback requires a long period of time and patients must make extreme efforts to achieve moderate improvement ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled trial (RCT) by Beurskens and colleagues, 112,113 patients with long-standing NFFP following BP, AN resection, VZV infection, and trauma receiving 3 months of comprehensive facial PT as opposed to being waitlisted demonstrated statistical improvements in patient-reported facial stiffness and FDI scores and quantitative assessment of lip length; however, no statistical benefit was seen in blinded expert-assessed FGS scores 12 months after therapy (level Ib). In the 2014 RCT by Pourmomeny and colleagues, 114 114 An RCT by Nicastri and colleagues 115 demonstrated that 74% of patients with BP presenting with severe to complete FFP (ie, HBG V/ VI) who received combination pharmacologic therapy (CPT) with prednisone and valacyclovir plus comprehensive PT within 10 days of symptom onset progressed to an HBG of I or II as assessed by 1 blinded expert within 6 months, compared with only 48% of those receiving CPT alone (adjusted P 5 .038) (level Ib). In summary, recent evidence supports the use of PT in acute FFP and long-standing NFFP.…”
Section: Physiotherapymentioning
confidence: 99%